经济发展和改革的历史性变化与增长方式的根本转变 - 刘伟 (中国远洋航务, 2006)
The major anticipated objectives of economic structural adjustmentswere to optimize and upgrade industrial structures and strengthen worldcompetitiveness. Levels of economic and social informatization should beenhanced and infrastructure further improved. The trend of wideningdevelopment gaps between regions should be effectively controlled and levelsof urbanization raised. Build new socialist rural areas, optimize and upgradeindustrial structures, promote concordant development of regions, build aconservation-minded and environment-friendly society, further system reformand enhance opening-up, efficiently practice strategies to invigorate Chinathrough science and education and through human resource development,and give impetus to constructing a socialist harmonious society.
Keywords: 根本转变; 增长方式; 经济发展; 历史性变化; 新兴工业化国家; 发展中国家; 加速时期; 经济增长; 社会主义市场经济体制; 市场化程度